Sex, Lies, and Surveys : The Role of Interviewer Characteristics - Koroknay-Palicz, Tricia (World Bank, Washington, DC, 2019)
This paper examines how easily observable interviewer characteristics, such as gender and physical attractiveness, and more difficult to observe characteristics, such as attitudes and beliefs, affect adolescent girls' disclosure of sexual behavior during a baseline survey for an adolescent girls program in Liberia. The study finds that girls are more likely to report sexual activity to better-looking interviewers, and less likely to do so to interviewers holding more discriminatory gender attitudes and greater expectations about the program. The study finds no evidence that the gender of the interviewer matters.